2022
DOI: 10.1177/23259671221120678
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Rich Plasma Versus Microfragmented Adipose Tissue for Knee Osteoarthritis: A Randomized Controlled Trial

Abstract: Background: Platelet-rich plasma (PRP) has been established as safe and effective for knee osteoarthritis (OA). Another orthobiologic therapy, microfragmented adipose tissue (MFAT), has gained attention because of its heterogeneous cell population (including mesenchymal stem cells). However, prospective comparative data on MFAT are lacking. Because of the safety, efficacy, and simplicity of PRP, new therapeutics such as MFAT should be compared directly with PRP. Purpose: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
27
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 43 publications
(67 reference statements)
1
27
0
Order By: Relevance
“…25 A randomized controlled trial comprising 58 patients with symptomatic Kellgren-Lawrence I-IV knee OA showed comparable Visual Analog Scale (VAS) and KOOS scores after leukocyte-rich PRP and micro-fragmented AT intra-articular injections (3.56 ± 4.62 million nucleated cells/ml) at 6-month follow-up. 26 Similarly, Kaszyński et al, 27 in their randomized controlled trial including 60 patients with Kellgren-Lawrence I-III symptomatic knee OA, showed comparable VAS, KOOS, Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), and IKDC 2000 outcomes between intra-articular LP-PRP and autologous AT injections at 12 months. Similarly, Zaffagnini et al, 28 in a randomized controlled trial, showed no significant differences in IKDC, KOOS, and EuroQol 5-dimensions questionnaire (EQ-5D) between a single intra-articular injection of microfragmented AT and PRP at 12-month follow-up.…”
Section: Discussionmentioning
confidence: 92%
“…25 A randomized controlled trial comprising 58 patients with symptomatic Kellgren-Lawrence I-IV knee OA showed comparable Visual Analog Scale (VAS) and KOOS scores after leukocyte-rich PRP and micro-fragmented AT intra-articular injections (3.56 ± 4.62 million nucleated cells/ml) at 6-month follow-up. 26 Similarly, Kaszyński et al, 27 in their randomized controlled trial including 60 patients with Kellgren-Lawrence I-III symptomatic knee OA, showed comparable VAS, KOOS, Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), and IKDC 2000 outcomes between intra-articular LP-PRP and autologous AT injections at 12 months. Similarly, Zaffagnini et al, 28 in a randomized controlled trial, showed no significant differences in IKDC, KOOS, and EuroQol 5-dimensions questionnaire (EQ-5D) between a single intra-articular injection of microfragmented AT and PRP at 12-month follow-up.…”
Section: Discussionmentioning
confidence: 92%
“…Recently, there has been increased interest in the use of autologous biologics, including platelet-rich plasma (PRP), adipose tissue, etc., for regenerative medicine applications, especially in musculoskeletal conditions such as knee osteoarthritis [ 9 ]. Numerous randomized controlled trials and meta-analyses have shown the safety and efficacy of PRP for the treatment of knee OA [ 10 ]; thus, PRP is considered the gold-standard biologic for the treatment of musculoskeletal injuries. On the other hand, other autologous treatment modalities such as adipose tissue (including microfragmented adipose tissue (MFAT)) have not undergone a similar degree of clinical trials [ 10 ].…”
mentioning
confidence: 99%
“…Numerous randomized controlled trials and meta-analyses have shown the safety and efficacy of PRP for the treatment of knee OA [ 10 ]; thus, PRP is considered the gold-standard biologic for the treatment of musculoskeletal injuries. On the other hand, other autologous treatment modalities such as adipose tissue (including microfragmented adipose tissue (MFAT)) have not undergone a similar degree of clinical trials [ 10 ]. Initial clinical studies have reported improved patient-reported outcomes in patients suffering from knee OA post-administration of MFAT [ 11 , 12 , 13 ].…”
mentioning
confidence: 99%
See 2 more Smart Citations